2015
DOI: 10.1590/1516-4446-2014-1583
|View full text |Cite
|
Sign up to set email alerts
|

Personality prototype as a risk factor for eating disorders

Abstract: Objective: To establish whether the risk of suffering from an eating disorder (ED) is associated with the high-functioning, undercontrolled, or overcontrolled personality prototype groups. Method: The Revised NEO Personality Inventory (NEO-PI-R) and the Eating Disorder Inventory 2 (EDI-2) were administered to 69 patients diagnosed as suffering from EDs (cases) and 89 people free of any ED symptoms (control group). A cluster analysis was carried out to divide the participants into three groups based on their sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Moreover adolescence is the period of onset of personality disorders ( 5 ). According to the literature, obsessive–compulsive and avoidant personality disorders are frequently associated to eating disorder ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover adolescence is the period of onset of personality disorders ( 5 ). According to the literature, obsessive–compulsive and avoidant personality disorders are frequently associated to eating disorder ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the first aim of this study, we identified the three prototypical Asendorpf personality patterns in a sample of people with Dm1 and in a control sample. These patterns showed different degrees of association with adherence to self-care guidelines for Dm1 and with psychological health factors, once again confirming the existence of these personality patterns that are differentially related to psychological phenomena [ 24 , 29 ]…”
Section: Discussionmentioning
confidence: 87%
“…They have been considered as indicators of adaptation and psychosocial adjustment in adolescents [ 27 ] and also as predictors of behavioral problems in children and adolescents [ 28 ]. Moreover, they have been related to increased risk of eating disorders [ 29 ] and have been used to estimate admission to a rehabilitation program for patients with spinal cord injuries [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 [ 11 14 ]). Both OC and UC personality types have been associated with a higher risk of developing an ED compared to resilient types [ 15 ] and comparable personality types are identified among patients presenting for treatment of depression [ 10 ]. Furthermore, classifying individuals who have EDs as OC, UC or resilient has been found to be more predictive of longitudinal outcomes in ED treatment (Described in more detail below; [ 16 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%